ANALISIS DINAMIK PADA SISTEM STRUKTUR KOMPL EKS MENGGUNAKAN METODE SINTESIS MODAL GANDA - LAELI HAJATI, NUR
The topic of this research study is the aplication of substructure method on complex structural analysis system for dynamical cases. By using the substructure method, it is possible to assemble, to inspect, and to analyze any component of structure individually. The restrain or boundary condition of the structure can be free, fix, or hybrid (combination or between free and fix). The studied structural procedure is double modal synthesis, using balance structural formula approaches in displacement function. Selected mode in first twentieth mode was done by Truncation of Rayleigh-Ritz Type and Truncation by Projection. The tested structural model is 3-dimension structure, which is comprise of two substructures with free-restrainment, i.e. space frame with beam elements and dome with shell element. Assembling of substructure is based Primal Problem. The exact value resulted from software simulation (the exact value is not resulted from experimental works), was used as reference of accurate numerical result. In general, double modal synthesis resulted not so much different with its exact value and this method can be used as good alternative structural analysis.